IMPLIKASI KEBIJAKAN PENDIDIKAN ERA SOEHARTO PADA EKSISTENSI MADRASAH - Toto Suharto (The Faculty of Tarbiyah and Teacher Training associated with PSPII, 2012)
This paper seeks to track a number of political trauma in Soeharto era (New Order) that befall of Islamic education, particularly in madrasah. The discussion is carried out historically and analytically to a number of policies and the implementation of Islamic historical facts under Suharto. Facts and data are reviewed through politics of Islamic education. The study results showed that in general education policies under Suharto are: 1) centralized, 2) discriminatory and 3) tends to be quantitative. They swapped back into the politicization of education in order to preserve power. One of the Islamic educational institutions that became the political victim of Soeharto was madrasah. Ijazaisme policy, equality and accreditation either through the Ministry of Religious Affairs and Education and Culture have managed to control the (quality of) the development of madrasah. Although the quantity of madrasah grew very rapidly but the quality is so low that made madrasah marginalized. Until now the madrasah is still considered 'the second-class schools'. The substance of the madrasah as a community empowerment was restricted by the Soeharto regime. As a result, it is still difficult to find qualified private madrasah which is equal/above average quality of the public school.